COMPARATIVE EVALUATION OF PUSHOUT BOND STRENGTH OF FIBER POST IN DIFFERENT REGIONS OF ROOT DENTIN USING SELF ADHESIVE AND SELF ETCH RESIN CEMENTS – AN IN VITRO STUDY - D.Y, Mallikarjunan; Noon, Assmee Mohammed; Revankar, Vanita D.; Senthamilselvan, Arun; Ganapathy, Aarthi; Ravikumar, Kaarunya (International Journal of Psychosocial Rehabilitation, 2020)
The present study was to compare the push-out bond strength of fibre posts to root dentin using different techniques of self -etch and self-adhesive resin cements in various regions of root canal dentin. 30 single rooted mandibular premolars extracted for orthodontic reasons with similar root dimensions were included in this study. The cleaning & shaping of root canals were done using crown-down technique in X Smart endomotor system. After 7 days of storage in 100% ambient humidity, the root canals were prepared using #2 preparation drill of fiber post system. #2 preparation drill of the post system was used and post spaces were prepared leaving 4mm of obturated point in the canal and teeth were divided into two groups of 15 each based on different techniques of cementation. In group 1 posts were luted with self adhesive cement and self etch resin cement in group 2. The test was performed in a universal testing machine at a speed of 1 mm/min. The universal testing machine induced a load in the apical to coronal direction of the post without applying any pressure to the cement or dentin. The bond strength in MPa was obtained with the formula- Bond strength (MPa) = Debonding force (N)/Total bonding area (S) (mm2). The real thickness of the slices (h) and the post diameter in coronal (r1)and apical (r2) were measured and the bonding area (S) was calculated by S = π (r1+ r2) √ (h2+(r1-r2)2 in mm2 for each slice. There is a significant difference in RELYX U2OO (MPa) among the different region (P